The Influence of Macroeconomics on GDP Growth - Gerald Nikki Tiendy; Valentino Budhidharma (Universitas Pelita Harapan, 2025)
This study investigates the relationship between macroeconomic factors and GDP Growth, with a focus on their collective impact on GDP growth across 185 countries from 2001 to 2022. Utilizing a panel data approach, this research explores how variables such as Aggregate Effective Tax Rate (AETR), Statutory Tax Rate (STR), Employment Growth (EG), Population (P), Control of Corruption (COC), and Tax Visit (TV) affect economic performance. The Fixed Effects Model is selected as the most appropriate estimation technique based on Chow and Hausman tests. The results reveal that AETR, EG, and P have significant positive effects on GDP growth, indicating that effective tax collection, labor expansion, and demographic growth are key drivers of macroeconomic performance. In contrast, STR, COC, and TV are found to have no statistically significant influence. Furthermore, Random Forest analysis identifies Population, Employment Growth, and Control of Corruption as the most important predictors, while model refinement shows that excluding the TV variable improves explanatory power. These findings suggest that tax policy effectiveness relies more on enforcement and demographic support than on nominal tax rates alone. The study offers insights for policymakers to design tax systems that align with broader economic goals and institutional capacities.